Valorization of sewage sludge through catalytic sub- and supercritical water gasification. Issue 4 (August 2020) - Yan, Mi; Hantoko, Dwi; Kanchanatip, Ekkachai; Zheng, Rendong; Zhong, Yingjie; Mubeen, Ishrat
Abstract: Sub- and supercritical water gasification is applied to recover energy from sewage sludge in a batch reactor. The effects of reaction temperature and water-soluble additives as catalysts on gasification were examined. The resultant products, including syngas, hydrochar and liquid residues were characterized. The rise of temperature without the presence of catalysts increased the yield of H2 (0.06 (350 °C) to 1.91 mol/kg (450 °C) and enhanced the gasification efficiency (1.29–19.61%), and decreased total organic carbon (TOC) by 68.50% in liquid residue. The changes in product distribution and characteristics of hydrochar and liquid residue implied that the organic matters in sewage sludge were dissolved and hydrolyzed in sub- and supercritical water, resulting in the production of syngas. The catalytic effect of different catalysts in relation to the H2 gas yield was in the following order: KOH > NaOH > Na2 CO3 ≈ K2 CO3 . In the case of catalytic supercritical water gasification at 400 °C, the highest molar fraction (37.28%) and yield of H2 (1.60 mol/kg) were obtained in the presence of KOH. Furthermore, the scanning electron microscopy (SEM) analysis indicated that a conversion and dissolution of the organic matters in sewage sludge to liquid and gas, produced a porous, fragmented structure and disintegrated surface of hydrochar. Graphical abstract: Image 1 Highlights: Valorization of sewage sludge was done via sub- and supercritical water gasification. Organic matters in sludge were decomposed and hydrolyzed in supercritical water. Detailed characterization of hydrochar was performed. The catalytic effect on H2 yield was: KOH > NaOH > Na2 CO3 ≈ K2 CO3 . Porous, fragmented structure and disintegrated surface of hydrochar was observed.